1954
DOI: 10.1346/ccmn.1954.0030102
|View full text |Cite
|
Sign up to set email alerts
|

Electron Microscopy of Clay Surfaces

Abstract: Improvements in replica techniques have made possible the high magnification study of textural characteristics and surface features of clay aggregrates found either in nature or in the laboratory. The most successful method of sample preparation involves pre-shadowing the specimen with platinum and backing this with a layer of carbon prior to removal of the clay with a suitable solvent.Data on orientation and packing of clay particles are readily obtained. The method is useful to investigate clays in which the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

1958
1958
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 9 publications
1
11
0
Order By: Relevance
“…Bates, Hildebrand, and Swineford (1950) described dispersed metahalloysite as tubular, and hypothesized that a tubular morphology was inherited from an endellite precursor, which was thought to have assumed tubular form in its original growth process. Comer and Turley (1955) and Bates and Comer (1955) examined several kinds of surface replicas prepared from undispersed endellite masses, and confirmed that the endellite particles, in fact, were tubular. While the use of replicas permitted electron microscopic observation of the surface of the mass, it must be pointed out that preparation of the replicas involves evacuation of the sample as the initial step, and endellite does dehydrate under vacuum.…”
Section: Previous Determinations Of the Morphology Of Endellitementioning
confidence: 84%
“…Bates, Hildebrand, and Swineford (1950) described dispersed metahalloysite as tubular, and hypothesized that a tubular morphology was inherited from an endellite precursor, which was thought to have assumed tubular form in its original growth process. Comer and Turley (1955) and Bates and Comer (1955) examined several kinds of surface replicas prepared from undispersed endellite masses, and confirmed that the endellite particles, in fact, were tubular. While the use of replicas permitted electron microscopic observation of the surface of the mass, it must be pointed out that preparation of the replicas involves evacuation of the sample as the initial step, and endellite does dehydrate under vacuum.…”
Section: Previous Determinations Of the Morphology Of Endellitementioning
confidence: 84%
“…Carbon replicas were reinforced by the polystyrene disc method described by Bates and Comer (1955) and were freed from the specimens by immersion in distilled water or in concentrated hydrofluoric acid. Clay particles were removed from the reinforced replicas by floating in alternate baths of concentrated hydrofluoric acid and 0.5~ sodium hydroxide until clean.…”
Section: Investigationmentioning
confidence: 99%
“…Clay particles were removed from the reinforced replicas by floating in alternate baths of concentrated hydrofluoric acid and 0.5~ sodium hydroxide until clean. Replicas were scored into approximate 2 mm squares and freed from the polystyrene reinforcement as described by Bates and Comer (1955). Replica squares were cleaned of polystyrene in several baths of ethylene dichloride before being picked up on standard 3 mm diameter, 300 mesh copper support grids.…”
Section: Investigationmentioning
confidence: 99%
“…Electron micrographs were taken of powder samples of plastic, semiflint and flint clays and of carbon replicas of flint and impregnated semiflint clays. The carbon replicas were prepared according to the procedure outlined by Bates and Comer (1955). The slices for the x-ray investigations were cut from samples on which the orientation had been recorded in the field.…”
Section: Texture Of the Claymentioning
confidence: 99%